CORPORATE GOVERNANCE AND OTHER FACTORS ON FIRM VALUE - Damayanti, Eka Budi; Almalita, Yuliani (E-Jurnal Akuntansi TSM, 2023)
The purpose of this research was to obtain empirical evidence about the effect of the board of directors, board of commissioner, commissioner independent, institutional ownership, managerial ownership, public ownership, family ownership, firm size, and profitability as independent variables to firm value as a dependent variable. The population in this research using non-financial companies that were listed in Indonesia Stock Exchange (IDX) from 2019-2021. The sample used for this research consists of 73 listed non-financial companies. The selection of this sample used the purposive sampling method with a total of 217 research data and the data analysis method in this research used multiple regression analysis. The result of this research indicated that the board of director, independent commissioner, and profitability have a positive effect on firm value. The board of commissioner and firm size have a negative effect on firm value while institutional ownership, managerial ownership, public ownership, and family ownership have not affected firm value